1993
DOI: 10.1128/iai.61.3.1141-1145.1993
|View full text |Cite
|
Sign up to set email alerts
|

Induction of bradyzoite-specific Toxoplasma gondii antigens in gamma interferon-treated mouse macrophages

Abstract: By using stage-specific monoclonal antibodies, an in vitro model has been developed to analyze the kinetics of expression of stage-specific antigens during the conversion process between tachyzoites and bradyzoites of Toxoplasma gondii. Following infection of murine macrophages with bradyzoites, the expression of bradyzoitespecific antigens declined, whereas the expression of tachyzoite-specific antigens increased during the first 72 h postinfection. Conversely, in gamma interferon-treated murine macrophages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
0
5

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(73 citation statements)
references
References 30 publications
1
67
0
5
Order By: Relevance
“…The same authors also observed that cell cultures inoculated with tachyzoites from the peritoneal exudate of mice had completely lost tachyzoitespecific markers by 72 HAI. Bohne et al [3] obtained similar results in cell cultures inoculated with bradyzoites. The bradyzoite-specific antigens declined from 100% to 15% from day 1 to 3 DAI of cultures.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The same authors also observed that cell cultures inoculated with tachyzoites from the peritoneal exudate of mice had completely lost tachyzoitespecific markers by 72 HAI. Bohne et al [3] obtained similar results in cell cultures inoculated with bradyzoites. The bradyzoite-specific antigens declined from 100% to 15% from day 1 to 3 DAI of cultures.…”
Section: Discussionmentioning
confidence: 61%
“…This is supported by studies on antigen expression as ascertained by the various bradyzoite specific sera available. Most bradyzoite specific monoclonal antibodies and recombinant polyclonal sera available are expressed after one day in culture under conditions which induce bradyzoite switching [3,4,35,361. The late appearing antigen is not seen until five to six days in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot studies have demonstrated that tachyzoites and bradyzoites are antigenically distinct [5,11,15,. Monoclonal antibodies specific to bradyzoites [3,15,20, 221 and tachyzoites [5] have been described. The development in vitro of bradyzoites and the conversion of bradyzoites isolated from mouse brains into tachyzoites has been demonstrated recently employing bradyzoite specific monoclonal antibodies [3, 191. In the present study, utilizing our previously developed bradyzoitespecific monoclonal antibodies, we describe a continuous cell culture system that allows for the in vitro study of bradyzoite development of T. gondii.…”
mentioning
confidence: 99%
“…Cysts from brains of mice that were mfected three months before were used as a controls for mature bradyzoites.In order to evaluate whether chemotherapeutic agents can also induce stage differentiation, murine bone marrowderived macrophages were infected with tachyzoites of T. gondii strain NTE, and were incubated in the presence of pyimethamine at different concentrations. Since previous experiments have shown that maximal expression of bradyzoite-specific antigens occurs on day 4 after infection, all cultures were evaluated on this day by determining the relative number of parasitophorous vacuoles expressing the MAb 4FS-reactive bradyzoite-specific antigen in an immunofluorescence assay [3].To determine whether the promoter of the bradyzoite-specific gene BAG1 [l] is stage-specifically regulated, the 5' promoter region of this gene was cloned upstream of the reporter gene encoding chloramphenicol acetyltransferase (CAT). Since the 3' flanking sequence has been shown to be not important for regulation of the B,4GI promoter, the 3' flanking region of SAGl was cloned downstream of the reporter gene.…”
mentioning
confidence: 99%
“…In order to evaluate whether chemotherapeutic agents can also induce stage differentiation, murine bone marrowderived macrophages were infected with tachyzoites of T. gondii strain NTE, and were incubated in the presence of pyimethamine at different concentrations. Since previous experiments have shown that maximal expression of bradyzoite-specific antigens occurs on day 4 after infection, all cultures were evaluated on this day by determining the relative number of parasitophorous vacuoles expressing the MAb 4FS-reactive bradyzoite-specific antigen in an immunofluorescence assay [3].…”
mentioning
confidence: 99%